Telemedicine in the United Kingdom current status and future prospects. - Istepanian, R.S.H.
The objective of this correspondence is to present an overview of some of the current developments and some of the ongoing telemedicine programs in the United Kingdom. The issues of the future integration of telemedicine activities within the National Health Service that promise better access to healthcare with higher efficiency, mobility, and lower cost are also discussed.
Keywords: National Health Service; United Kingdom; Cost; Current status; Future prospects; Healthcare; Telemedicine